Status and factors related to post‐traumatic growth in continuous ambulatory peritoneal dialysis: A multi‐centre study. Issue 1 (17th October 2021) - Li, Xing; Zhou, Xueli; Ma, Dengyan; Salerno, Stephen; Qi, Min; Diao, Yongshu; Chen, Chongcheng; Zhong, Hui; Xiao, Shuxin; Wang, Yan; Zhang, Jiaju; Luo, Hongyan; et al.
Abstract: Aim: To investigate the extent of post‐traumatic growth, and the correlation between post‐traumatic growth and self‐perceived stress, post‐traumatic growth and self‐perceived burden among CAPD patients. Design: A cross‐sectional study. Methods: This was a multi‐centre study including 752 patients from 44 hospitals. Self‐perceived stress, self‐perceived burden and post‐traumatic growth were measured using the post‐traumatic growth inventory (PTGI), the Chinese version of the perceived stress questionnaire (CPSQ) and the self‐perceived burden scale (SPBS). A multiple stepwise regression analysis was fit with the total PTGI score as the outcome of interest. Results: Patients concurrently experienced post‐traumatic growth and stress following peritoneal dialysis. The initiation of patients' education level, employment status and self‐perceived stress were all found to relate to growth among Chinese CAPD patients. There was not sufficient evidence to suggest that self‐perceived burden was related to experiencing growth.